Uma práxis docente humanizadora, com crianças, em um bairro educador da cidade de São Paulo - Barreto Neta, Lormina (2021)
This research seeks to answer the following question: What are the possibilities and limits of a humanizing educational praxis, with children, in a public school that declares the intention to work in a citizen perspective in the context of a Educating Neighborhood (Bairro Educador)? The general objective is to analyze what to teach as a humanizing teacher in the context of an educational experience committed to the participatory experience of children; as for as specific objectives, the conception of childhood present in this educational space will be identified, as well as evidence of a humanizing teaching in the practice of the research subjects and in the political pedagogical project of the school. It is also intended to announce notes for teacher training consistent with what makes humanizing teachers. The fundamentals of the study are based on the perspective of the Sociology of Childhood, in which the child is considered a subject of law and a producer of culture. Paulo Freire is the main reference to understand the role of the educator in different learning contexts. For the methodology, the investigation takes a qualitative approach, which postulates understanding as a fundamental element for analyzing reality, in view of the various human and social interactions that are revealed by the interpretation that is made of the experienced facts. The research is conducted in a public school in São Paulo, Brazil, that follows the model of “Bairro Educador”, which integrates the school as a collective space for participation in the life of the community. The subjects are teachers from the first three years of elementary school, two coordinators and the director of the school. The research is developed through bibliographic study and documents analysis. For the research type, it was chosen case study and empirical material. For empirical data collection, a structured interview was conducted with teachers, school coordinators and the school principal. The political-pedagogical project was also the object of examination. It is expected that this work can contribute to other forms of education. The detailed analysis of the research findings concludes that humanizing education is possible with children from 6 to 8 years old, if the education is based on the possibility of transforming people who can transform the world or is close to the Freirean concepts dreamed for public education. Emef Presidente Campos Salles is the example that the collective research for being more, makes dreams possible